Influence Of Website Interactivity On Online Users' Behavior And Attitude - A Marketing Point Of View - Zadeh, Ali Zeinolabedin (2009)
In the present study, the researcher examined if the increased level of interactivity of a website had positive effects on the web users' attitudes, behaviors, and experience online in the context of hotel web sites, a crucial point of debate among researchers and an assumption that is inconclusive, contradictory, and inconsistent in the extant literature. The researcher also examined the consequences of actual user-site interactivity, specifically how actual user-site interactivity, i.e., from a behavioral perspective rather than an intentional perspective, influences web users' attitudes and behaviors toward websites.